Preparation method and application of high-entropy alloy aerogel for electro-catalysis

The preparation of high-entropy alloy aerogels by one-step reduction method solves the problem of poor phase separation and stability of traditional catalysts during electrocatalytic nitrate reduction, and achieves high-efficiency electrocatalytic nitrate reduction at low overpotentials, with excellent catalytic activity and stability.

CN119571369APending Publication Date: 2025-03-07HUNAN NORMAL UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411769606.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing high-entropy alloy aerogel catalysts have problems of phase separation and poor electrocatalytic stability in the process of electrocatalytic nitrate reduction, which limits their application.

Method used

A high-entropy alloy aerogel is prepared by one-step reduction method. By quickly mixing inorganic metal salts with sodium borohydride and other reducing agents, a high-entropy alloy aerogel with a cross-linked network structure is formed, which improves its electrocatalytic activity and stability.

Benefits of technology

High-efficiency electrocatalytic nitrate reduction at low overpotentials was achieved, with excellent catalytic activity and stability, and the yield and Faraday efficiency of NH3 and 98.31% under ultra-low overpotentials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571369A_ABST
    Figure CN119571369A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ammonia synthesis and electro-catalysis, and particularly relates to a preparation method and application of high-entropy alloy aerogel for electro-catalysis. The preparation method comprises the following steps: mixing an inorganic metal salt in a solvent to obtain a precursor solution, quickly adding a reducing agent, standing, and washing and drying the obtained product to obtain the high-entropy alloy aerogel catalyst, the inorganic salt is selected from five or more of copper salt, cobalt salt, iron salt, nickel salt, palladium salt, gold salt, ruthenium salt, platinum salt and silver salt. The three-dimensional continuous porous reticular high-entropy alloy aerogel is obtained through one-step reduction of the inorganic metal salt and standing assembly, the high-entropy alloy aerogel prepared through the method is high in reduction assembly speed, phase separation of multi-component alloy can be effectively inhibited, an amorphous alloy structure is obtained, and therefore when the high-entropy alloy aerogel is applied to ammonia production through electro-catalysis nitrate reduction, the high-entropy alloy aerogel can be used for preparing the high-entropy alloy aerogel. And excellent electrochemical activity and stability can be presented in an ultra-low overpotential range of-0.2 to + 0.2 V vs.RHE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ammonia synthesis and electrocatalysis, and specifically relates to a preparation method and application of a high entropy alloy aerogel for electrocatalysis. Background Art

[0002] Ammonia (NH3) is an important basic chemical for the synthesis of agricultural nitrogen fertilizers, medicines, dyes and plastics, and is regarded as a carbon-free hydrogen-rich fuel due to its high hydrogen content (17.6wt%) and mature storage method. It is widely used in chemical, pharmaceutical, biological and national defense fields, and is an important resource for human survival and development. At present, the industrial synthesis of NH3 still mainly relies on the traditional Haber-Bosch process, which not only requires high temperature (300-500℃) and high pressure (200-350atm) conditions, but also produces a large amount of carbon dioxide gas, which inevitably aggravates the greenhouse effect and accelerates global warming. Moreover, excessive nitrate is currently discharged into surface water and groundwater due to overfertilization and industrial pollution, which seriously threatens human health and life. Therefore, using environmental conditions to electrocatalyze the reduction of nitrates to NH3 can not only reduce energy consumption, reduce carbon emissions, and reduce production safety hazards, but also promote wastewater denitrification and achieve environmental remediation.

[0003] The key to achieving efficient electrocatalytic nitrate reduction to produce NH3 is to develop electrocatalysts with high catalytic activity and selectivity and low overpotential. However, although traditional single metal catalysts have good reactivity in the electrocatalytic nitrate reduction reaction, they cannot take into account both high selectivity and high Faraday efficiency. At the same time, there are problems such as oxidative dissolution and corrosion leaching in the electrochemical process. Alloying is an effective way to solve the problems related to single metal catalysts. The introduction of different metals leads to alloying between different metals, thereby anchoring the easily soluble metal. At the same time, the introduction of other metals also effectively regulates the catalytic activity and selectivity of electrocatalytic nitrate production of NH3. However, binary alloys often have their catalytic activity dominated by a single metal due to the corresponding adjustment of their component ratios. High entropy alloys have more element selection and higher composition adjustability, and their high mixing entropy also brings higher physical and chemical stability. So far, high entropy alloy catalysts have been applied in the fields of electrochemical hydrogen evolution, oxygen evolution and carbon dioxide reduction, and have shown excellent reactivity, selectivity and stability. They are regarded as promising emerging materials in the field of electrocatalysis. However, the high entropy alloy catalysts currently used for electrocatalytic nitrate production of NH3 are mainly high entropy alloy aerogel catalysts prepared by the freeze-thaw method. This catalyst still has problems such as easy phase separation and poor electrocatalytic stability, which restricts its application. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a stable high entropy alloy aerogel electrocatalyst with high catalytic activity, high selectivity and low overpotential. The aerogel exhibits excellent catalytic activity and stability in electrocatalytic nitric acid reduction to produce NH3 at low overpotential, which solves the problems of easy phase separation and poor electrocatalytic stability of high entropy alloy aerogel catalysts prepared by traditional freeze-thaw method.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a method for preparing a high entropy alloy aerogel, which is specifically: firstly, an inorganic metal salt is mixed in a solvent to obtain a precursor solution, then a reducing agent is quickly added, and after being fully mixed, the solution is allowed to stand for a treatment, and after standing for a treatment, the obtained product is washed and dried to obtain the high entropy alloy aerogel catalyst; the inorganic metal salt is selected from five or more of copper salts, cobalt salts, iron salts, nickel salts, palladium salts, gold salts, ruthenium salts, platinum salts, and silver salts, and in the precursor solution, the molar proportion of each metal element is 5 to 40%.

[0007] Preferably, the inorganic metal salt is selected from copper salts, cobalt salts, nickel salts, platinum salts and ruthenium salts.

[0008] The present invention selects five specific metal elements of copper, cobalt, nickel, platinum and ruthenium to prepare high entropy alloy aerogel, and uses sodium borohydride as a reducing agent to form a high entropy alloy aerogel with a cross-linked network structure. The aerogel exhibits excellent catalytic activity and stability in electrocatalytic nitric acid reduction to produce NH3 at low overpotential.

[0009] Preferably, in the precursor solution, the molar ratio of each metal element is 15-25%. Within this range, the metals are more conducive to forming high configuration entropy and alloy structure, and the metals are evenly distributed in the high entropy alloy aerogel.

[0010] Preferably, the static treatment is static treatment at room temperature for 12 to 24 hours. The sediment is aggregated by static treatment for a long time to form a stable gel state, while excessive static treatment will affect the element valence state on the surface of the gel.

[0011] Preferably, the molar ratio of the inorganic metal salt to the reducing agent is 1:1 to 1:10.

[0012] Preferably, the reducing agent is selected from one or more of ascorbic acid, sodium borohydride, hydrazine hydrate, and sodium sulfite. More preferably, the reducing agent is sodium borohydride. Sodium borohydride is used to reduce inorganic metal salts, and this dosage can ensure complete reduction without excessively etching the metal to affect the morphology and size of the metal aerogel.

[0013] Preferably, the washing is a solvent replacement for 5 to 6 times, with a total time of 1 to 2 days. The solvent used for the replacement is selected from one or more of water, ethanol, acetone and tert-butyl alcohol. The replacement of the solvent effectively ensures that the structure of the gel is not damaged, and the residual soluble reducing agent and soluble inorganic metal salt can be fully removed after multiple exchanges.

[0014] Preferably, the solvent is selected from any one or more of water, ethanol and tert-butanol.

[0015] Preferably, the inorganic metal salt refers to a soluble salt of a metal, including one of chloride, sulfate, and nitrate, etc. For example, cupric chloride dihydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, ruthenium trichloride, chloroplatinic acid hexahydrate, etc.

[0016] Preferably, the drying is freeze drying, which is non-directional freeze drying, with a freezing temperature of -80 to -20°C and a freezing time of 0.1 to 10 hours; a drying temperature of 0 to 15°C, a drying vacuum of 1 to 20 Pa, and a drying time of 2 to 3 days.

[0017] The second aspect of the present invention provides a high entropy alloy aerogel prepared by the preparation method described in the first aspect.

[0018] The third aspect of the present invention provides the use of the high entropy alloy aerogel described in the second aspect in the electrocatalytic nitrate reduction reaction to produce ammonia.

[0019] The high entropy alloy aerogel electrocatalyst prepared by the method of the present invention has an appropriate aerogel skeleton diameter and a high specific surface area. The average diameter of the CuNiCoPtRu high entropy alloy aerogel skeleton is about 20.14nm; the specific surface area is 58.15m 2 ·g -1 At the same time, the high entropy alloy aerogel electrocatalyst prepared by the method of the present invention has a cross-linked network structure and a high specific surface area, and can be used as a cathode material for efficient electrocatalytic reduction of nitrate to NH3. The catalyst exhibits excellent electrochemical activity and stability. The NH3 yield and Faraday efficiency of CuNiCoPtRu high entropy alloy aerogel at -0.05V vs.RHE are as high as 3.36mmol·h -1 cm -2 The NH3 yield and Faraday efficiency of other five-element and above high entropy alloy aerogels can reach 2.8-3.2 mmol·h -1 cm -2 and 92~97%.

[0020] In addition, the high entropy alloy aerogel composite material prepared by the method of the present invention can also be used as an electrode material in the manufacture of lithium-ion batteries and supercapacitors. Accordingly, the use of the above-mentioned high entropy alloy aerogel composite material as an electrode material or in the preparation of an electrode material is also within the protection scope of the present invention.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention discloses a method for preparing an amorphous high entropy alloy aerogel, wherein an inorganic metal salt is first mixed in a solvent to obtain a precursor solution, and then a reducing agent is quickly added. After standing, the obtained product is washed and dried to obtain the high entropy alloy aerogel catalyst; the inorganic salt is selected from five or more of copper salts, cobalt salts, iron salts, nickel salts, palladium salts, gold salts, ruthenium salts, platinum salts, and silver salts. The present invention reduces the inorganic metal salt in one step, and obtains a three-dimensional continuous porous mesh high entropy alloy aerogel after standing and assembling. The method prepares the high entropy alloy aerogel, and because of its fast reduction and assembly rate, the phase separation of the multi-element alloy can be effectively suppressed to obtain an amorphous alloy structure. The high entropy alloy aerogel prepared by the method of the present invention is applied to electrocatalytic nitrate reduction to produce ammonia, and can exhibit excellent electrochemical activity and stability in the ultra-low overpotential range of -0.05V vs.RHE. Specifically, the present invention has the following advantages:

[0023] (1) The present invention obtains a high entropy alloy aerogel catalyst by a one-step method. The method is simple and efficient, has a short preparation cycle, good reproducibility, is easy to scale up, and is suitable for industrial production.

[0024] (2) The catalyst of the present invention has a good cross-linked network structure, a large specific surface area, and a good mass transfer effect. It has better activity and stability than traditional alloy aerogels in the electrocatalytic reduction of nitrates to produce NH3.

[0025] (3) The present invention utilizes a rapid reduction method to effectively inhibit the phase separation of the high entropy alloy aerogel, causing it to form a single-phase amorphous alloy structure, thereby further enhancing its electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the high entropy alloy aerogel catalyst of Example 1;

[0027] Figure 2 This is a transmission electron microscope image of the high entropy alloy aerogel catalyst of Example 1;

[0028] Figure 3 This is a spectrum scan image of the high entropy alloy aerogel catalyst of Example 1;

[0029] Figure 4is an X-ray diffraction pattern of the high entropy alloy aerogel catalyst of Example 1;

[0030] Figure 5 This is the nitrogen DFT pore size distribution diagram of the high entropy alloy aerogel catalyst of Example 1;

[0031] Figure 6 Linear sweep voltammetric curves of electrocatalytic nitrate reduction to produce NH3 by the high entropy alloy aerogel catalyst of Example 1 and copper aerogel, copper cobalt nickel aerogel, cobalt nickel platinum ruthenium aerogel prepared in Comparative Examples 1, 2, 3, 4, and the high entropy alloy aerogel catalyst prepared by freeze-thaw method;

[0032] Figure 7 NH3 yield graph of the high entropy alloy aerogel catalyst of Example 1 and the copper aerogel, copper cobalt nickel aerogel, cobalt nickel platinum ruthenium aerogel prepared in Comparative Examples 1, 2, 3, 4 and the high entropy alloy aerogel catalyst prepared by freeze-thaw method when electrocatalyzing nitrate reduction to produce NH3 at a potential of -0.05V vs. RHE;

[0033] Figure 8 A Faraday efficiency diagram of the high entropy alloy aerogel catalyst of Example 1 and copper aerogel, copper cobalt nickel aerogel, platinum cobalt nickel ruthenium aerogel prepared in Comparative Examples 1, 2, 3, 4, and a high entropy alloy aerogel catalyst prepared by freeze-thaw method when electrocatalyzing nitrate reduction to produce NH3 at a potential of -0.05V vs. RHE;

[0034] Fig. 9 This is a test graph of the electrocatalytic stability of the high entropy alloy aerogel catalyst of Example 1 and the high entropy alloy aerogel catalyst of Comparative Example 4 prepared by the freeze-thaw method. DETAILED DESCRIPTION

[0035] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0037] Example 1: A one-step method for preparing a five-element high entropy alloy aerogel comprises the following steps:

[0038] (1) Dissolve 17.1 mg of copper chloride dihydrate, 23.8 mg of cobalt chloride hexahydrate, 23.8 mg of nickel chloride hexahydrate, 20.7 mg of ruthenium trichloride and 51.8 mg of chloroplatinic acid hexahydrate in 50 mL of deionized water and stir for 10 min until the mixture is well mixed to form a precursor solution.

[0039] (2) Quickly (within 1 second) add 36.8 mg of sodium borohydride to the solution obtained in step (1), stir well for 15 minutes, and then let stand for 12-24 hours.

[0040] (3) The solid-liquid mixture obtained in step (2) is replaced with deionized water 5-6 times over a period of 1 day to obtain a solid-liquid mixture in which the solution portion except the product is colorless and transparent.

[0041] (4) The solid-liquid mixture obtained in step (3) is placed at -50°C for freeze-drying for 2-3 days to obtain a black product copper-cobalt-nickel-platinum-ruthenium high entropy alloy aerogel catalyst.

[0042] like Figure 1 As shown in the scanning electron microscope image, the high entropy alloy aerogel obtained in this embodiment has a three-dimensional continuous porous structure. Figure 2 As shown, the high entropy alloy aerogel obtained in this embodiment has a cross-linked network structure, and the average diameter of the aerogel skeleton is about 20.14nm. Figure 3 As shown in the energy spectrum scanning image, the high entropy alloy aerogel obtained in this embodiment has an alloy phase structure, and each metal element is evenly distributed on the aerogel skeleton. Figure 4 The X-ray diffraction image of the high entropy alloy aerogel obtained in this example has a broad diffraction peak and no characteristic diffraction peak, indicating that the crystallinity of this example is poor and there is no significant phase separation. Figure 5 As shown, the high entropy alloy aerogel obtained in this embodiment has a high specific surface area: the pore size of its mesopores is 2.8nm; the specific surface area is 58.15m 2 ·g -1 .

[0043] Comparative Example 1: Preparation of copper aerogel

[0044] A single metal aerogel was prepared according to the preparation process of Example 1, except that: in step (1), 85.2 mg of copper chloride dihydrate was dissolved in 50 mL of deionized water, and the mixture was stirred for 10 min until the mixture was uniformly mixed to form a precursor solution.

[0045] The ternary alloy aerogel was prepared according to the preparation process of Example 1, except that: in step (1), 28.5 mg of cupric chloride dihydrate, 40.0 mg of cobalt chloride hexahydrate and 40.0 mg of nickel chloride hexahydrate were dissolved in 50 mL of deionized water, and stirred for 10 min until the mixture was uniformly mixed to form a precursor solution.

[0046] Comparative Example 3: Preparation of Cobalt-Nickel-Pt-Ru aerogel

[0047] The quaternary alloy aerogel was prepared according to the preparation process of Example 1, except that: in step (1), 30.0 mg of cobalt chloride hexahydrate, 30.0 mg of nickel chloride hexahydrate, 28.9 mg of ruthenium trichloride and 65.8 mg of chloroplatinic acid hexahydrate were dissolved in 50 mL of deionized water, and stirred for 10 min until the mixture was uniformly mixed to form a precursor solution.

[0048] Comparative Example 4: Five-element high entropy alloy aerogel prepared by freeze-thaw method

[0049] The five-element alloy aerogel was prepared according to the preparation process of Example 1, except that: step (2) was to quickly add 36.8 mg of sodium borohydride to the precursor solution obtained in step (1), mix for 15 minutes, and then freeze it with liquid nitrogen for 5 minutes. After pre-thawing at room temperature for 15 minutes, it was placed in a water bath (25-30°C) until completely thawed, and then allowed to stand for 12-24 hours.

[0050] Experimental Example 1: Experiment on the electrocatalytic reduction of nitrate to produce NH3 by high entropy alloy aerogel

[0051] A dispersion with anhydrous ethanol and nafion in a volume ratio of 19:1 was prepared, and then the aerogel catalysts of Example 1 and Comparative Examples 1-4 were added to the dispersion, and then the dispersion containing the catalyst was dropwise coated on carbon paper, which was used as a working electrode after being purged and dried with an inert gas. The counter electrode was 1×1 cm 2 The reference electrode is a mercury / mercury oxide electrode, and the cathode / anolyte is 1M KOH+1000ppm KNO3-N / 1M KOH. First, a linear sweep voltammetry test is performed: the test curve is +0.4~-0.6V vs.RHE, and the sweep rate is 10mV·s -1 . Then the chronopotentiometry test was performed: the test potential was -0.05Vvs.RHE, the time was 1h, and the above tests were all IR compensated by 80%. The cathode electrolyte was sampled before and after the chronopotentiometry, and the indigo blue colorimetric method was used for color development and then the absorbance was measured using a UV-visible spectrophotometer. The NH3 concentration was obtained from the standard curve, and the NH3 yield and Faraday efficiency were calculated by the following formula:

[0052]

[0053] Where c is the difference in NH3 concentration in the cathode electrolyte before and after the chronoamperometry (ppm), V is the volume of the cathode electrolyte (mL), and A is the electrode area (cm 2 ), t is the chronoamperometry test time (h), M is the molar mass of NH3 (17.03), and n is the molar mass of NO3 - is the number of electrons transferred to NH3 (8), F is the Faraday constant (96485 C / mol), and Q is the charge consumed in the chronoamperometry test (C).

[0054] like Figure 6 As shown, compared with the copper aerogel, copper cobalt nickel aerogel, cobalt nickel platinum ruthenium aerogel and high entropy alloy aerogel prepared by freeze-thaw method in comparative examples 1, 2, 3 and 4, the high entropy alloy aerogel electrocatalyst obtained in Example 1 exhibits a significant nitrate reduction advantage. Specifically, the high entropy alloy aerogel electrocatalyst obtained in Example 1 exhibits the most positive starting potential (+0.365V vs. RHE) and the highest nitrate reduction response current, which can show 800mA·cm at an ultra-low potential of only -0.132V vs. RHE. -2 , while the copper aerogel, copper-cobalt-nickel aerogel, cobalt-nickel-platinum-ruthenium aerogel and high entropy alloy aerogel prepared by freeze-thaw method in comparative examples 1, 2, 3 and 4 required -0.286, -0.215, -0.159 and -0.161 V vs. RHE, respectively.

[0055] like Figure 7 As shown in Figure 1, the high entropy alloy aerogel electrocatalyst obtained in Example 1 obtained 3.36 mmol·h at a potential of -0.05 V vs. RHE. -1 cm -2 The ultra-high ammonia yield is higher than that of the copper aerogel, copper-cobalt-nickel aerogel, cobalt-nickel-platinum-ruthenium aerogel prepared in Comparative Examples 1, 2, 3, and 4, and the high entropy alloy aerogel prepared by freeze-thaw method (0.59 mmol·h -1 cm -2 , 2.59mmol·h -1 cm -2 , 2.89mmol·h -1 cm -2 , 2.9mmol·h -1 cm -2 ), indicating that the high entropy alloy aerogel prepared in Example 1 effectively optimized the adsorption and conversion capacity of nitrate through high entropy and one-step gelation.

[0056] like Figure 8As shown, the high entropy alloy aerogel electrocatalyst obtained in Example 1 can achieve a high NH3 Faraday efficiency of 98.31% at a low overpotential of -0.05V vs. RHE, and the NH3 Faraday efficiency at the same overpotential is better than the copper aerogel, copper cobalt nickel aerogel, cobalt nickel platinum ruthenium aerogel and high entropy alloy aerogel prepared by freeze-thaw method (58.29%, 93.39%, 97.87%, 98.13%) prepared in Comparative Examples 1, 2, 3, and 4, indicating that the high entropy alloy aerogel prepared in Example 1 successfully achieves efficient electrocatalytic reduction of nitrate to NH3.

[0057] like Fig. 9 As shown, the high entropy alloy aerogel electrocatalyst obtained in Example 1 has excellent stability in electrocatalytic nitrate reduction to produce NH3. After 6 cycles, the ammonia yield of the catalyst obtained in Example 1 at a potential of -0.05V vs. RHE still maintains more than 90% of the initial value, while the ammonia yield of the high entropy alloy aerogel prepared by the freeze-thaw method in Comparative Example 4 has decayed to less than 50% of the initial value after 6 cycles, indicating that the high entropy alloying method of the present invention successfully enhances the phase structure stability of the aerogel catalyst in the process of electrocatalytic nitrate reduction to NH3.

[0058] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing a high entropy alloy aerogel, characterized in that: First, an inorganic metal salt is mixed in a solvent to obtain a precursor solution, and then a reducing agent is quickly added. After being fully mixed, the solution is allowed to stand for a treatment. After standing for a treatment, the obtained product is washed and dried to obtain the high entropy alloy aerogel catalyst; the inorganic metal salt is selected from five or more of copper salts, cobalt salts, iron salts, nickel salts, palladium salts, gold salts, ruthenium salts, platinum salts, and silver salts.

2. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The inorganic metal salt is selected from copper salts, cobalt salts, nickel salts, platinum salts and ruthenium salts.

3. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: In the precursor solution, the molar ratio of each metal element is 15-25%.

4. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The static treatment is to stand at room temperature for 12 to 24 hours.

5. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The molar ratio of the inorganic metal salt to the reducing agent is 1:1 to 1:

10.

6. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The reducing agent is selected from one or more of ascorbic acid, sodium borohydride, hydrazine hydrate and sodium sulfite.

7. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The washing is performed by replacing the solvent 5 to 6 times, and the total time is 1 to 2 days.

8. The method for preparing a high entropy alloy aerogel according to claim 1, characterized in that: The solvent is selected from any one or more of water, ethanol and tert-butanol.

9. High entropy alloy aerogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high entropy alloy aerogel according to claim 9 in the electrocatalytic nitrate reduction reaction to produce ammonia.

Citation Information

Cited By

  • Method for preparing diacetylmonoxime by electro-catalytic co-reduction of nitrate and butanone

    CN120250002A

  • Preparation method and application of high-entropy nano-sponge CuNiFePdPt catalyst

    CN121123307A